Pengenalan Manajemen SDM Untuk Posyandu Dikelurahan Serua Indah - Eko Sudarso; Muhamad Arif; Ali Zaenal (Universitas Pamulang, 2024)
This research aims to provide an introduction to HR management at Posyandu in Serua Indah Village. The methods used are counseling, training and direct assistance to Posyandu managers and volunteers. The material presented includes the basic principles of HR management, timeand resource management, as well as the importance of communication and teamwork in improving Posyandu performance. The results of this service are expected to increase theunderstanding and skills of Posyandu managers in managing human resources effectively. In this way, it is hoped that the Posyandu in Serua Indah Subdistrict can operate more efficiently and be able to provide better health services for the community, especially mothers andchildren.Keywords: HR Management